Experimental work on decontamination of wastewaters containing organic dye by liquid phase micro extraction method. Issue 6 (13th April 2021) - Abbasi, Ali; Seifollahi, Zahra; Rahbar-Kelishami, Ahmad
ABSTRACT: Nowadays, the innovative processes for refining industrial dye wastewater are often used to reduce the toxicity of these pollutants due to satisfy the treatment standards. This paper presents a study on the removal of methylene blue (MB) and thymol blue (TB) dyes from contaminated water using a mono-and di-ester mixture(MDEHPA) as the extractant in a Y-Y junction microchannel. Operating parameters such as aqueous solution pH, and extractant and residence time were optimized. The maximum rates of TB and MB extraction were achieved to be 97.9% and 98.4%, respectively. Mass transfer performance is surveyed using overall volumetric mass transfer coefficient determination ( k L α ). GRAPHICAL ABSTRACT: